The set theoretical approach to the problems of pursuit - Shoykhet, B.; Petrosjan, L. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. А. Шойхет, Л. А. Петросян. Теоретико-множественный подход к играм преследованияB. Šojchetas, L. Petrosianas. Aibių teorija ir persekiojimo uždaviniai